The Interactionist Self and Grounded Research: Reflexivity in a Study of Emergency Department Clinicians - Nugus, Peter (Qualitative Sociology Review, 2008)
This paper shows how the theory of symbolic interactionism shaped a grounded investigation of the organizational labor of Australian Emergency Department (ED) clinicians. Further, it shows how symbolic interactionism supports reflexive criteria for validating grounded research. Using ethnographic methods across two metropolitan EDs, interactionism’s emphasis on roles applied equally to the relationship between researcher and participants as to the relationships among participants. Specifically, the researcher generated data by positioning interactionism as the mediator of the emergent relationship between researcher and participants. The results of this positioning were: a traceable path from understanding to interpretation and the search for consequentiality rather than truth. Interactionism facilitated the co-production by the researcher and participants of limits on the generalizability of the data. The paper is an argument for symbolic interactionism as a means not merely to generate sociological findings, but to conceptualize the impact of the researcher on the grounded research process.